2009
DOI: 10.1111/j.1365-294x.2009.04447.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Antarctic minke whales unusually abundant because of 20th century whaling?

Abstract: Severe declines in megafauna worldwide illuminate the role of top predators in ecosystem structure. In the Antarctic, the Krill Surplus Hypothesis posits that the killing of more than 2 million large whales led to competitive release for smaller krill-eating species like the Antarctic minke whale. If true, the current size of the Antarctic minke whale population may be unusually high as an indirect result of whaling. Here, we estimate the long-term population size of the Antarctic minke whale prior to whaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 52 publications
(107 reference statements)
1
28
0
Order By: Relevance
“…Laws (1977) proposed that minke whales in the Antarctic may have increased as a result of the decimation of the larger species. However, more recent genetic analysis indicating large pre-and postexploitation minke whale populations in Antarctic waters does not support the idea that minke whales have been limited by competition with larger baleen whales for krill (Ballance et al, 2006;Ruegg et al, 2010). (Nor does it support the hypothesis that large minke numbers may be inhibiting recovery of large baleen whales today.…”
Section: Whales As Ecosystem Structuring Agentsmentioning
confidence: 98%
“…Laws (1977) proposed that minke whales in the Antarctic may have increased as a result of the decimation of the larger species. However, more recent genetic analysis indicating large pre-and postexploitation minke whale populations in Antarctic waters does not support the idea that minke whales have been limited by competition with larger baleen whales for krill (Ballance et al, 2006;Ruegg et al, 2010). (Nor does it support the hypothesis that large minke numbers may be inhibiting recovery of large baleen whales today.…”
Section: Whales As Ecosystem Structuring Agentsmentioning
confidence: 98%
“…It had been suggested that these populations had competed with penguins for the same food sources, mainly krill, and that the decreases in the populations of marine mammals allowed some species of seabirds, including penguins, to increase in abundance (Trivelpiece and Volkman 1979). This so-called krill surplus hypothesis has been challenged and does not appear to be valid for minke whales (Ruegg et al 2010). However, it is still invoked to explain the population dynamics of other krill predators.…”
Section: Introductionmentioning
confidence: 99%
“…Other scientists feel that this system is driven from bottom up control, with environmental conditions dictating the abundance of krill in the system. Debate continues on both sides of the discussion in marshalling evidence to support either "top down" or "bottom up" explanations (see Ruegg et al 2010, Huang et al 2014.…”
Section: Whales and Southern Ocean Food Websmentioning
confidence: 97%